Image Classification Schemes Based on Sliced Radial Energy Distribution of DFT and the Statistical Moments of Haar Wavelet - Abbas, Hashim; George, Loay E. (Iraqi Journal of Science, 2020)
Texture recognition is used in various pattern recognition applications and texture classification that possess a characteristic appearance. This research paper aims to provide an improved scheme to provide enhanced classification decisions and to decrease processing time significantly. This research studied the discriminating characteristics of textures by extracting them from various texture images using discrete Haar transform (DHT) and discrete Fourier transform DFT. Two sets of features are proposed; the first set was extracted using the traditional DFT, while the second used DHT. The features from the Fourier domain are calculated using the radial distribution of spectra, while for those extracted from Haar Wavelet the statistical distribution of various relative moments was adopted. Four types of Euclidean distance metrics were used for classification decisionpurposes. The considered method was applied on 475 classes of textures belonged to 32 sets from Salzburg Texture Image Database, each set holding 16 images per class, so the a total of 7600 images were tested. Each image was separated into seven bands of color component (i.e., red, green, blue, and gray….). Concepts of average and standard deviation were calculated to determine the inter/intra scatter analysis for each feature to find out the best discriminating features that can be used.The final result of DHT was 99.98 for the testing sets and 99.71 for the training sets, while the final result of DFT was 98.63 for the testing sets and 93.74 for the training sets.